No Condition Is Permanent : Middle Class in Nigeria in the Last Decade - Corral Rodas, Paul Andres; Molini, Vasco; Oseni, Gbemisola (Taylor and Francis, 2018)
The economic debate on the existence and definition of the middle class has become particularly lively in many developing countries. Building on a recently developed framework called the Vulnerability Approach to Middle Class (VAMC) to define the middle class, this paper tries to estimate the size of the Nigerian middle class in a rigorous quantitative manner and to gauge its evolution over time. Using the VAMC method, the middle class group can be defined residually from the vulnerability analysis as those for which the probability of falling into poverty is below a certain threshold. The results show that there has been considerable improvement in the size of the Nigerian middle class from 13 per cent in 2003/4 to 19 per cent in 2012/13. However, the rate has been slower than expected given the high growth rates experienced in the country over the same period. The results also paint a heterogeneous picture of the middle class in Nigeria with large spatial differences. The southern regions have a higher share and experienced more growth of the middle class compared with the northern regions.